2004
DOI: 10.1074/jbc.m311604200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Induces an Inositol 1,4,5-Trisphosphate-dependent Increase in Nuclear and Cytosolic Calcium in Cultured Rat Cardiac Myocytes

Abstract: In the heart, insulin-like growth factor-1 (IGF-1) is a pro-hypertrophic and anti-apoptotic peptide. In cultured rat cardiomyocytes, IGF-1 induced a fast and transient increase in Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 68 publications
5
79
0
Order By: Relevance
“…These same agonists also promote hypertrophic growth of neonatal cardiac myocytes [104,105]. Studies using immunostaining, Western blotting and analysis of mRNA have suggested that IP 3 R types 1, 2 and 3 are expressed in neonatal cells [102,103,106].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These same agonists also promote hypertrophic growth of neonatal cardiac myocytes [104,105]. Studies using immunostaining, Western blotting and analysis of mRNA have suggested that IP 3 R types 1, 2 and 3 are expressed in neonatal cells [102,103,106].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…Almost all studies that examined either the distribution of IP 3 Rs, or the spatial pattern of IP 3 -evoked Ca 2+ signals, have reported that the channels are largely expressed in close proximity to the nucleus in neonatal cells [102,103,[106][107][108]. This is unlike RyRs, which have a more widespread expression pattern in neonatal cells [102].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…Primary cultures of cardiomyocytes were cultured from hearts of 1-to 3-day-old Sprague-Dawley rats seeded on gelatin-coated coverslips and starved in serum-free medium 24 h prior to the experiment. The protocol produces cultures of cardiac myocytes that are at least 95% pure (30).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac myocytes were prepared as described in ref. 30. Primary cultures of cardiomyocytes were cultured from hearts of 1-to 3-day-old Sprague-Dawley rats seeded on gelatin-coated coverslips and starved in serum-free medium 24 h prior to the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiomyocytes were isolated from Pkd2 ϩ/ϩ and Pkd2 Ϫ/Ϫ embryos at embryonic day 17.5 and cultured by using a method as described with a few modifications (46). Ca 2ϩ imaging experiments were performed by using fluo-4-loaded cells, which then were observed with a Zeiss LSM510 confocal microscope (47).…”
Section: Isolation Of Mouse Cardiomyocytes and Ca 2؉ Imaging Experimementioning
confidence: 99%